Nasopharyngeal biopsy in adults presenting with serous otitis media: Cross‐sectional study. Issue 7 (14th March 2018) - Shilo, Shahaf; Abu‐Ghanem, Sara; Yehuda, Moshe; Weinger, Anat; Fliss, Dan M.; Abergel, Avraham
Abstract: Background: The purpose of this study was to investigate the association between isolated serous otitis media (SOM) and/or conductive hearing loss (CHL) and nasopharyngeal carcinoma (NPC) in a low‐to‐intermediate endemic area. Methods: Medical records of all adult patients (≥17 years) with SOM/CHL who underwent endoscopic‐guided nasopharyngeal biopsy to exclude NPC during a 10‐year period were reviewed. Statistical analyses were conducted to identify significant predictors for NPC. Results: A total of 195 patients were included (121/195; 62.1% men), among whom 169 (86.7%) presented with isolated SOM/CHL. Overall, 12 patients were diagnosed with NPC (12/195; 6.2%), however, only 1 patient (1/169; 0.6%) had isolated SOM/CHL. Coexisting clinical manifestations and suspicious nasopharyngeal findings on fiber‐optic nasopharyngoscopy were found to be significant predictors for NPC on univariate and multivariate analyses ( P < .05). Conclusion: Patients with isolated SOM/CHL and without coexisting clinical manifestations or suspicious findings on nasopharyngoscopy may avoid a routine nasopharyngeal biopsy.